Tantangan Santri Ponpes Rakha Dalam Menghadapi Era Disrupsi - Syahabudin Nur; Siti Zainab (Yayasan Asy-Syifa Amuntai Selatan, 2023)
The development of an increasingly advanced era makes students more demand that students are not only capable in the field of religion (religious) but students must also be able to overcome or face this era of disruption, This means that students are not only superior in the field of religion but also excel in the field of education Science and Technology. In this research study, the writer uses descriptive method-qualitative, data collection techniques, namely the interview process, observation, and documentation at the Rasyidiyah Khalidyah Amuntai Islamic boarding school. Results This study shows that Rakha Islamic Boarding School students are able to compete and following the development of an increasingly advanced era in the era of disruption, where innovation and creativity are highly demanded which then becomes a challenge separately for Rakha Islamic Boarding School students. The Rakha education system has the goal is to produce students who excel in science and technology and etiquette, supporters and obstacles in the formation of the character of the santri, as well as the role of the kyai or mu'allim in building the character of students in the face of the era of disruption without eliminating old traditions and customs that have existed since the beginning The establishment of the Rakha Islamic Boarding School until now is in the midst of a century.